2016
DOI: 10.1155/2016/4173138
|View full text |Cite
|
Sign up to set email alerts
|

Brief Overview on Nitinol as Biomaterial

Abstract: Shape memory alloys remember their shape due to thermoelastic martensitic phase transformation. These alloys have advantages in terms of large recoverable strain and these alloys can exert continuous force during use. Equiatomic NiTi, also known as nitinol, has a great potential for use as a biomaterial as compared to other conventional materials due to its shape memory and superelastic properties. In this paper, an overview of recent research and development related to NiTi based shape memory alloys is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 85 publications
0
65
0
2
Order By: Relevance
“…Superiority of Nitinol to stainless steel and Ti-Al-V for endochondral bone substitution has be explained by other authors [25]. Tarnita et al have shown Nitinol resemblance to the bone [37] by indicating self-locking, self-expanding, and self-compression attests [20,23,[38][39][40]. Another preference of Nitinol to stainless steel is insensitiveness to the magnetic resonance [41,42] which eliminates the debris movement concern during the spinal imaging examination.…”
Section: Nitinolmentioning
confidence: 99%
“…Superiority of Nitinol to stainless steel and Ti-Al-V for endochondral bone substitution has be explained by other authors [25]. Tarnita et al have shown Nitinol resemblance to the bone [37] by indicating self-locking, self-expanding, and self-compression attests [20,23,[38][39][40]. Another preference of Nitinol to stainless steel is insensitiveness to the magnetic resonance [41,42] which eliminates the debris movement concern during the spinal imaging examination.…”
Section: Nitinolmentioning
confidence: 99%
“…46 This is likely related to the shape memory effect of nitinol. 47 During clot retrieval, the microcatheter is minimally advanced onto the detachment zone of the stentriever, and the entire stentriever-microcatheter assembly is pulled back as a unit. Aspiration needs to be applied to the guide catheter throughout this retrieval process, to prevent NTE.…”
Section: Intervention Phasementioning
confidence: 99%
“…Last but not least, pre-operative management plays an essential role and needs to be taken into account for favorable outcomes, as Table 1 presents. Implants used for osteosynthesis are manufactured using iron-based alloys such as surgical grade stainless-steel 316L, titanium-based alloys, cobalt-chromium-based composites, or shape-memory alloys [23][24][25]. Of these, stainless-steel 316L is the most commonly used, due to its cost-effectiveness and good integration of corrosion resistance and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%